Efek ekstrak sambiloto (Andrographis paniculata) terhadap ekspresi matrix metalloproteinase-1 dan hipertrofi jantung pada mencit yang terpapar asap rokok - I Made Agus Endra Permana; I Nyoman Wiryawan; Wayan Aryadana; I Gde Raka Widiana; I Gusti Kamasan Nyoman Arijana; I Made Satria Yudha Dewangga (Intisari Sains Medis, 2021)
Introduction: Sambiloto (Andrographis paniculata) is a plant that is often used in traditional medicine and is known to have antioxidant, anti-inflammatory and cardiovascular effects. There are many studies of sambiloto on inflammatory markers, but there is no study on the effect of sambiloto on MMP-1 expression. The purpose of this study was to determine the effect of sambiloto on MMP-1 expression and cardiac hypertrophy in mice exposed to cigarette smoke.Methods: This research is an experimental analytic study with a randomized post test only control group design. Thirty-two healthy male Swiss Webster mice aged 8-10 weeks weighing 20-30 grams were divided into 4 groups, namely: control group (standard feed + exposure to cigarette smoke), P1 (standard feed + exposure to cigarette smoke + sambiloto extract 18 mg/ kg BW), P2 (standard feed + exposure to cigarette smoke + sambiloto extract 29 mg/kg BW), P3 (standard feed + exposure to cigarette smoke + sambiloto extract 40 mg/kg BW). All groups were followed for 60 days.Results: There was a significant difference in MMP-1 expression between the control group and all treatment groups. There were significant differences in MMP-1 expression between groups P1 and P2, and between P1 and P3 groups. There was a significant difference in heart weight/weight ratio between the control group and all treatment groups. There was a significant difference in the heart weight/body weight ratio between the P1 and P3 groups.Conclusion: The administration of sambiloto extract decreased the expression of MMP-1 with a tendency for its effect to increase with increasing dose and the optimal dose was found in the sambiloto extract 29 mg/kg BW. The difference in the effect of sambiloto extract on cardiac hypertrophy only appeared after the dose was increased to 40 mg/kg BW Latar Belakang: Sambiloto (Andrographis paniculata) merupakan tanaman yang sering dipakai dalam pengobatan tradisional dan diketahui mempunyai efek antioksidan, anti inflamasi dan efek pada sistem kardiovaskular. Terdapat banyak penelitian sambiloto terhadap marker inflamasi, tetapi belum ada penelitian tentang efek ekstrak sambiloto terhadap ekspresi MMP-1. Tujuan dari penelitian ini untuk mengetahui efek ekstrak sambiloto terhadap ekspresi MMP-1 dan hipertrofi jantung pada mencit yang terpapar asap rokok.Metode: Penelitian ini adalah penelitian analitik eksperimental dengan rancangan randomized post test only control group design. Tiga puluh dua mencit Swiss Webster jantan sehat berumur 8-10 minggu dengan berat 20-30 gram dibagi menjadi 4 kelompok yaitu: kelompok kontrol (pakan standar + paparan asap rokok), P1 (pakan standar + paparan asap rokok + ekstrak sambiloto 18 mg/kg BB), P2 (pakan standar + paparan asap rokok + ekstrak sambiloto 29 mg/kg BB), P3 (pakan standar + paparan asap rokok + ekstrak sambiloto 40 mg/kg BB). Semua kelompok diikuti selama 60 hari.Hasil: Terdapat perbedaan signifikan ekspresi MMP-1 antara kelompok kontrol dengan semua kelompok perlakuan. Terdapat perbedaan signifikan ekspresi MMP-1 antara kelompok P1 dengan P2, dan antara P1 dengan P3. Terdapat perbedaan signifikan rasio berat jantung/berat badan antara kelompok kontrol dengan semua kelompok perlakuan. Terdapat perbedaan signifikan rasio berat jantung/berat badan antara kelompok P1 dengan P3. Simpulan: Pemberian ekstrak sambiloto menurunkan ekspresi MMP-1 dengan kecenderungan efeknya meningkat dengan peningkatan dosis dan dosis optimal terdapat pada ekstrak sambiloto 29 mg/kg BB. Perbedaan efek ekstrak sambiloto terhadap hipertrofi jantung baru muncul setelah dosis ditingkatkan menjadi 40 mg/kg BB.